Supplementation of Calcium and Vitamin D Reduces Colonic Inflammation and Beta-Catenin Signaling in C57BL/6 Mice Fed a Western Diet. (29th May 2020) - Zeng, Huawei; Safratowich, Bryan; Liu, Zhenhua; Bukowski, Michael; Ishaq, Suzanne
Abstract: Objectives: Adoption of a Western diet, low in calcium and vitamin D (CaD), is a global problem leading to increased obesity, colonic inflammation and neoplasia. However, the mechanisms underlying this relationship remains to be elucidated. We tested the hypothesis that CaD supplementation may reduce colonic inflammation, oncogenic signaling and dysbiosis in the colon of C57BL/6 mice fed a Western diet. Methods: Male C57/BL6 mice (4-week old) were assigned to 3 dietary groups (n = 20/group) for 36 weeks: (1) AIN76A as a control diet (AIN); (2) a defined rodent "new Western diet" (NWD); or (3) NWD with CaD supplementation (NWD/CaD). We used biochemical, mass spectrometry, histological and multi-omics approaches to determine the interplay between CaD supplementation, colonic inflammation and microbiome composition. Results: Mice receiving the NWD or NWD/CaD exhibited >0.2- fold increase in the concentrations of plasma leptin, tumor necrosis factor α (TNF-α) and body weight when compared with those on the AIN diet. However, the concentrations of plasma interleukin 6 (IL6), inflammatory cell infiltration and b-catenin/Ki67 protein (oncogenic signaling) were increased >0.8 - fold in the NWD (but not NWD/CaD) group when compared with the AIN group. Consistent with the inflammatory phenotype: (1) colonic secondary bile acid (an inflammatory bacterial metabolite) concentrations increased >0.4 - fold in the NWD group when compared with the NWD/CaD and AIN groups; (2) in contrast, α diversity of colonic bacterial species, a healthy gut microbiome marker, was decreased by 30% in the NWD group when compared with the AIN and NWD/CaD groups. Conclusions: This study demonstrates that, in a mouse model, CaD supplementation reduces colonic inflammation, oncogenic signaling and bacterial dysbiosis in the context of Western diet consumption. Funding Sources: This work was supported by U.S. Department of Agriculture, Agricultural Research Service, research project 3062–51, 000-056–00D.